Internalizing symptoms and chronotype in youth: A longitudinal assessment of anxiety, depression and tripartite model. (February 2019) - Haraden, Dustin A.; Mullin, Benjamin C.; Hankin, Benjamin L.
Highlights: Circadian preferences develop across the lifespan. Eveningness ("night owl") is associated with depression and anxiety. Adolescents have greater eveningness and higher risk for depression and anxiety. Specificity of eveningness to anxiety, and longitudinal direction are unclear. Eveningness is linked to depression and low positive affect in youth. Abstract: Biological rhythm theories highlight the reciprocal relations between dysregulated circadian patterns and internalizing psychopathology. Chronotype characterizes individuals' diurnal preference, as some exhibit more morningness or eveningness. Previous research suggests that eveningness prospectively predicts depression in adolescence. Anxiety often co-occurs with depression, but little is known about longitudinal, reciprocal associations between chronotype and anxiety, and whether this relationship remains after controlling for depression. We assessed different forms of anxiety (social, panic, separation), positive/negative affect, anxious arousal (from tripartite theory), and depression, in relation to chronotype to better understand the specificity and directionality of associations between chronotype and internalizing problems in adolescence. Community youth participated in three assessment time points: T1, T2 (18-months post-T1), and T3 (30-months post-T1) as part of a larger longitudinal study. Youth completed self-report measures of anxiety, depression, positive and negative affect, and chronotype. Regression analyses showed that eveningness: (1) concurrently associated with decreased separation anxiety, elevated symptoms of depression and low levels of positive affect, (2) was prospectively predicted by elevated depression, (3) did not predict later symptoms of anxiety. The reciprocal, prospective relationship between chronotype and internalizing psychopathology is specific to depression during adolescence.